Effect of Binahong Leaf Extract and Types of Sugars on Chemical and Sensory Characteristics of Cashew Milk - Puyanda, Irvia Resti; Supriyanto, Jamal; Mustofa, Akhmad (Journal of Innovative Food Technology and Agricultural Product, 2025)
Cashews are one of the plants that are the mainstay of local food for export in Indonesia. From the process of processing cashews into cashews ready for consumption, there is broken cashews, often called cashew waste. Because most people are looking for cashews that are still intact, so to increase the selling price value of cashews that are not intact, there needs to be innovation in their processing. The advantage of cashews is that they are high in unsaturated fats. The purpose of this study is to determine the effect of the addition of binahong leaf extract and type of sugar on the chemical and sensory characteristics of cashew milk. This study uses a Complete Random Design (RAL) which is arranged factorially of two factors of comparison of binahong leaf extract 2%, 4% and 6%. Types of sugar added to cashew milk, palm sugar, brown sugar, and granulated sugar. Data analysis using ANOVA with Duncan test. The results of the chemical test of cashew milk and the type of sugar had a real effect on antioxidant activity, dissolved protein content, fat content, ash content, redness, yellowness, taste like, and cashew milk aroma. However, the effect is not real in terms of total sugar content, brightness, color preference, and overall liking. The best chemical test results were A3B2 (6% extract comparison with brown sugar) with antioxidant activity results of 13.01%, total sugar content 25.25%, dissolved protein content 3.06%, fat content 3.37%, ash content 0.79%, brightness 69.72, redness 1.69, yellowness 17.34. The best sensory test results were A1B2 with 3.55 color preferences, aroma preferences 3.75, taste preferences 3.50 and overall preferences 3.50. keywords: binahong, sugar, cashew milk